Hypothesis testing equilibrium in signaling games - Lan Sun (Bielefeld University, Center for Mathematical Economics (IMW), 2016)
In this paper, we propose a definition of Hypothesis Testing Equilibrium (HTE) for general signaling games with non-Bayesian players nested by an updating rule according to Hypothesis Testing model characterized by Ortoleva (2012). An HTE may be different from a sequential Nash equilibrium because of the dynamic inconsistency. However, when player 2 only takes zero-probability message as an unexpected news, an HTE is a refinement of sequential Nash equilibrium and it survives Intuitive Criterion, but not vice versa. We provide existence theorem covering a broad class of signaling games often studied in economics, and the constrained HTE is unique in such signaling games.
urn:nbn:de:0070-pub-29035369
Keywords: 330; Signaling Games; Hypothesis Testing Equilibrium; Equilibrium Refinement